Modele przestrzenno-czasowe w benchmarkingu regionalnym - Sobczak, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The subject of the hereby study is regional benchmarking understood as a way of conducting activities which result in the region's development, by means of performing an on-going comparative analysis against competitive regions. It consists in the evaluation of relations between the studied region and the one which is best in a given class, followed by utilising its experiences in further performance.One of the tools which facilitate such comparison of particular regions, the identification of pattern regions, so called benchmarks, as well as the understanding of reasons which underlie the existing regional disproportions, become spatial-time econometric models.The objective of this study is the presentation of the concept of spatial-time models and opportunities for their use in regional benchmarking. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 74-83